PENGARUH KOMBINASI TRICHOKOMPOS DENGAN PUPUK UREA TERHADAP PRODUKSI TANAMAN SAWI (Brassica juncea L.) - Bagus, Arizal Muhammad (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
The aim of this research is to determine giving of the Trichocompos with urea fertilizer to found the best combination toward of the growth and plant production of mustard (Brassica juncea L.). this research conducted on August to December 2015. The research based on Completely Randomized Design (CRD) consisting of 5 treatments as follows: 0 ton/ha Empty Oil Palm Bunches (TKKS) Trichocompostwith 0 kg/ha urea Fertilizer (P0), 10 ton/ha Empty Oil Palm Bunches (TKKS) Trichocompost with 60 kg/ha urea (P1), 10 ton/ha Empty Oil Palm Bunches (TKKS) Trichocompostwith 100 kg/ha urea (P2), 15 ton/ha Empty Oil Palm Bunches (TKKS) Trichocompost with60 kg/ha urea (P3) and 15 ton/ha Empty Oil Palm Bunches (TKKS) Trichocompostwith 100 kg/ha urea (P4). The parameter that observed are : height of the plant, number of leaf, wide of leaf, fresh weight of plant/m2 and fresh weight of plant proper to consumtion/m2. The result of this research showed that giving of combination Empty Oil Palm Bunches (TKKS) Trichocompost with Urea fertilizer can stimulant growth that contain of the parameter height of the plant, number of leaf, wide of plant, fresh weight of plant/m2 and fresh weight of plant proper to consumption/m2. The giving of combination treatment 15 ton/ha Trchocompos TKKS with 100 kg/ha urea is the best dosage can produce the fresh weight plant of mustard 16,15 ton/ha.   Keywords: Trichocompos, Urea fertilizer.